Freeze concentration of coffee extract: study of block and falling-film techniques (2015)
Coffee is the most traded food in the world. The sensory and functional properties of the product are highly important for the consumers, and therefore, technologies that promote quality preservation are highly valued in coffee processing. In the production of freeze-dried coffee, freeze concentration is used to remove water from the extract. Water removal in freeze concentration is achieved by cooling the solution until ice crystals form and separate. Freeze concentration is a technology known for its ability to preserve the quality of the product thanks to low processing temperatures. Three techniques are used according to ice crystal growth: suspension, film (progressive or falling-film) and block (total or partial). Suspension freeze concentration is the most implemented technique at the industrial level, however, it requires complex systems for ice separation and many moving parts, which increases the initial and operating costs. For this reason, other techniques such as falling-film freeze concentration, and block freeze concentration are being developed seeking to reduce operational costs. In the present work, block and falling-film freeze concentration techniques used to concentrate aqueous coffee extract were studied. Equipment to study those techniques was designed and implemented. The effect of the operational variables of block and falling-film freeze concentration on separation efficiency was established. Preservation of bioactive compounds, volatile compounds, antioxidant activity, and sensory quality of the coffee extract when using freeze concentration was demonstrated. Finally, an operational strategy was proposed to integrate the studied techniques. Separation efficiency obtained with this process was comparable to industrial standards.